2005
DOI: 10.1111/j.1460-9568.2005.04378.x
|View full text |Cite
|
Sign up to set email alerts
|

The SDF‐1/CXCR4 pathway and the development of the cerebellar system

Abstract: Mice deficient for the chemokine receptor CXCR4 show premature translocation of granule cell neuroblasts from their germinal zone into the nascent cerebellum [Y.-R. Zuo et al. (1998) Nature, 393, 595-599]. Here, we used CXCR4-null mice to analyse the early development of cerebellar cortical inhibitory interneurons and pontine neurons which, in the adult, are synaptically integrated with granule cells. Cortical inhibitory interneuronal precursors normally invade the cerebellar anlage of CXCR4-deficient mice, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 38 publications
3
48
1
Order By: Relevance
“…Together, these data suggest that Pax2 should be perceived as a marker for early diVerentiating interneuronal precursors. Finally, it is only after they leave the ventricular epithelium that inhibitory interneuronal precursors become positive for Pax2 (Maricich and Herrup 1999); cf also Vilz et al 2005 andZordan et al 2008) which again is in keeping with the observation of Herrup and associates (Maricich and Herrup 1999) that Pax2-positive cells, in contrast to ventricular epithelia, are strictly neuronogenic.…”
Section: Development and Diverentiation Of Cerebellar (Cortical) Inhisupporting
confidence: 84%
“…Together, these data suggest that Pax2 should be perceived as a marker for early diVerentiating interneuronal precursors. Finally, it is only after they leave the ventricular epithelium that inhibitory interneuronal precursors become positive for Pax2 (Maricich and Herrup 1999); cf also Vilz et al 2005 andZordan et al 2008) which again is in keeping with the observation of Herrup and associates (Maricich and Herrup 1999) that Pax2-positive cells, in contrast to ventricular epithelia, are strictly neuronogenic.…”
Section: Development and Diverentiation Of Cerebellar (Cortical) Inhisupporting
confidence: 84%
“…5d), suggesting that the two signalling mechanisms may run parallel. Vilz 34 indicated that Plxnd1 expression is selectively abrogated in pontine nuclei neurons in Cxcr4 o/o mice, in contrast to other cerebellar populations (for example, inferior olive) and forebrain neurons. So, in order to biochemically explore a putative interaction of the two signalling pathways, we used COS1-transfected cells ( Fig.…”
Section: Sema3e or Plexind1 Absence Increased Cr Cells Migrationmentioning
confidence: 99%
“…The resulting differences in cell adhesivity may be invoked, according to the differential adhesion hypothesis (Steinberg, 1963;Foty and Steinberg, 2005) as one potential determinant of the rather unimpeded passage of the IGL by Pax2-positive inhibitory interneuronal precursors destined for the molecular layer. This interpretation is not contradicted that these latter cells, despite the fact that they express M-, N-and R-cadherin at levels comparable to Math1-EGFP positive granule cell neuroblasts, are strictly excluded from the EGL (Vilz et al, 2005;Weisheit et al, 2006). Rather, this pinpoints the fact that adhesive systems other than the cadherins under scrutiny here are clearly involved in cerebellar histogenesis.…”
Section: Quantitative Aspects Of Cadherin Expression -Cellular Interamentioning
confidence: 61%
“…Therefore, we analyzed the location of inhibitory interneuronal precursors versus that of cells of the granule cell lineage in reaggregate cultures. The availability of GFP-labeled interneuronal precursors allowed us to modify this assay such as to eliminate time consuming and artifact prone tissue processing (Vilz et al, 2005), as whole aggregates could be optically sectioned and analyzed (Fig 6G-P and Q-T). Thus, nascent or manipulated aggregates, which were too frail to withstand embedding and sectioning, became amenable to analysis.…”
Section: Cadherin Functionalitymentioning
confidence: 99%
See 1 more Smart Citation